IN VITRO PLANT REGENERATION FORM SHOOT TIP EXPLANTS OF HIBISCUS SYRIACUS (L.) - SUMAN KUMARI; R. K. PANDEY (The Bioscan, 2011)
The effect of Tributyltin chloride on freshwater bivalve, Lamellidens marginalis was assessed. The freshwater bivalves were exposed to 3.5, 2.5, 1.8 and 1.0 ppm experimental concentration (50% lethal concentration) of Tributyltin chloride up to 96 hours. After 24, 48, 72 and 96 h of exposure the lipid level were estimated in gonad, gill and digestive gland. The results showed a decrease in lipid in both the tissues with an increase in concentrations and time of exposure to the Tributyltin chloride.